Identification of AnnexinA1 as an Endogenous Regulator of RhoA, and Its Role in the Pathophysiology and Experimental Therapy of Type-2 Diabetes - Purvis, Gareth S. D.; Collino, Massimo; Loiola, Rodrigo A.; Baragetti, Andrea; Chiazza, Fausto; Brovelli, Martina; Sheikh, Madeeha H.; Collotta, Debora; Cento, Alessia; Mastrocola, Raffaella; Aragno, Manuela; Cutrin, Juan C.; et al. (Frontiers in Immunology, 2019)
Annexin A1 (ANXA1) is an endogenously produced anti-inflammatory protein, which plays an important role in the pathophysiology of diseases associated with chronic inflammation. We demonstrate that patients with type-2 diabetes have increased plasma levels of ANXA1 when compared to normoglycemic subjects. Plasma ANXA1 positively correlated with fatty liver index and elevated plasma cholesterol in patients with type-2 diabetes, suggesting a link between aberrant lipid handling and ANXA1. Using a murine model of high fat diet (HFD)-induced insulin resistance, we then investigated (a) the role of endogenous ANXA1 in the pathophysiology of HFD-induced insulin resistance using ANXA1-/- mice, and (b) the potential use of hrANXA1 as a new therapeutic approach for experimental diabetes and its microvascular complications. We demonstrate that: (1) ANXA1-/- mice fed a HFD have a more severe diabetic phenotype (e.g. more severe dyslipidemia, insulin resistance, hepatosteatosis and proteinuria) compared to WT mice fed a HFD; (2) treatment of WT-mice fed a HFD with hrANXA1 attenuated the development of insulin resistance, hepatosteatosis and proteinuria. We demonstrate here for the first time that ANXA1-/- mice have constitutively activated RhoA. Interestingly, diabetic mice, which have reduced tissue expression of ANXA1, also have activated RhoA. Treatment of HFD-mice with hrANXA1 restored tissue levels of ANXA1 and inhibited RhoA activity, which, in turn, resulted in restoration of the activities of Akt, GSK-3β and eNOS secondary to re-sensitization of IRS-1 signaling. We further demonstrate in human hepatocytes that ANXA1 protects against excessive mitochondrial proton leak by activating FPR2 under hyperglycaemic conditions. In summary, our data suggest that a) ANXA1 is a key regulator of RhoA activity, which restores IRS-1 signal transduction and b) recombinant human ANXA1 may represent a novel candidate for the treatment of T2D and/or its complications.